Analisis Disiplin Pengelolaan Keuangan Usaha Mikro dan Kecil Kabupaten Pohuwato Provinsi Gorontalo - Muhammad Anas; Sulaiman Sulaiman (FRONTIERS: JURNAL SAINS DAN TEKNOLOGI, 2018)
The aim of this research is to analysis the financial management discipline of micro and small enterprises at Pohuwato region. Gorontalo Province. The length aim of this research is the best practice for the micro and small enterprises. The method of this research is used quantitative research. while collecting data is used observation and questionnaire by applying multiple regression. The result of this research shows that the competencies of the enterprises and commitment of financial management for the enterprises having a positive influence towards the discipline of financial management for micro and small enterprises at Pohuwato Region, Gorontalo Province. this case is shown by statistical analysis, where the enterprises’ competencies in partial shows that the t calculation is bigger than t table or 6.549 > 1.968; While, the financial commitment also having a positive and significant influence; this case canbe shown by t calculation is bigger than T table, or 4.035 > 1.968. Simultaneously, both independent variables (enterprises’ competencies and financial management commitment also having positive and significance influences towards financial management of micro and small enterprises towards financial management of micro and small enterprises. this case can be shown by F calculation is bigger than F table. This case can be interpreted that micro andsmall enterprise is having a good of awareness, for learning a discipline of a good financial management; the other side that micro and small enterprises having a high financial commitment for developing their enterprises in the future.Keywords: Discipline of Financial Management, entrepreneur competence and financial commitment of Micro and Small Busine